2015
DOI: 10.1016/j.bpj.2015.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigations into the Mechanics of a Muscle Anchoring Complex

Abstract: The titin-telethonin complex, essential for anchoring filaments in the Z-disk of the sarcomere, is composed of immunoglobulin domains. Surprisingly, atomic force microscopy experiments showed that it resists forces much higher than the typical immunoglobulin domain and that the force distribution is unusually broad. To investigate the origin of this behavior, we developed a multiscale simulation approach, combining minimalist and atomistic models (SOP-AT). By following the mechanical response of the complex on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…One explanation would be the improvement of mitochondrial oxidative phosphorylation (discussion see below) and the increased expression of telethonin due to a modulation of the ubiquitin proteasome system (see Figure 4 ). Telethonin anchors the N-terminal region of titin in the Z-disk [ 37 ] and as an adapter protein it links myofibrillar components with the membranous beta-subunit of the I(Ks) channel [ 38 ]. In addition, telethonin knockdown leads to embryonic paralysis, myocyte defects and sarcomeric disruption [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation would be the improvement of mitochondrial oxidative phosphorylation (discussion see below) and the increased expression of telethonin due to a modulation of the ubiquitin proteasome system (see Figure 4 ). Telethonin anchors the N-terminal region of titin in the Z-disk [ 37 ] and as an adapter protein it links myofibrillar components with the membranous beta-subunit of the I(Ks) channel [ 38 ]. In addition, telethonin knockdown leads to embryonic paralysis, myocyte defects and sarcomeric disruption [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We present here a few recent studies supporting these concepts: Dima and coworkers showed that the conformational diversity attained via excursions on the conformational landscape underlie the mechanosensing functionality of a muscle anchoring complex observed in atomic force microscopy (AFM) [27]; Gur et al showed that the reconfiguration of adenylate kinase between its open and closed forms upon ligand binding takes place along such valleys of the conformational space [28]. Further, the conformational pathways described by a single mode starting from the open state were shown to successfully predict the closed state for a set of proteins that undergo large hinge-bending motions [29].…”
Section: Introductionmentioning
confidence: 98%